Reflections on the Metacultural Nature of Intangible Cultural Heritage - Markus Tauschek (Journal of Ethnology and Folkloristics)
One of the most central findings of recent heritage research in cultural anthropology points to heritage as a social process and as the result of a metacultural operation. This article discusses the metacultural nature of heritage by focusing on the history of heritage both as a concrete social practice and as a powerful concept of cultural policy. For heuristic reasons, the article tends to put the conceptualisation of heritage as a metacultural product in question and proposes to translate concepts from ritual studies into heritage research.